Frequency of non-asthma-like symptoms of allergic diseases based on ISAAC results in adolescents of the Khabarovsk region, Russia - E. N. Suprun; S. V. Suprun; M. S. Shkunova; E. I. Yakovlev; R. S. Telepneva; O. A. Lebed'ko; G. P. Evseeva (Association of Paediatric Allergists and Immunologists of Russia (APAIR), 2023)
Background. In the course of the ISAAC standardized survey, not only asthma-like symptoms are revealed, but also other atopy symptoms, the prevalence of which in their relationship with asthma-like symptoms is of great interest for determining the likelihood of developing BA. This work presents the first study of the frequency of symptoms occurrence in school students of the Khabarovsk Territory (Russia).Materials and methods. The survey involved 696 teenagers living in the city of Khabarovsk and Khabarovsk rural district who meet the requirements of the ISAAC program method by age (13-14 years).Results. The prevalence of symptoms of allergic rhinitis in all interviewed adolescents of the Khabarovsk Territory was 69.3 %. In the group with asthma-like symptoms it is significantly higher (77.2 % versus 56.6 %). Complications in the form of conjunctivitis with non-infectious rhinitis occurred in 12.6 % of cases, and also much more often in children with asthma-like symptoms (30.1 % versus 8.9 %). Symptoms of atopic dermatitis occur in 11.8 % of adolescents, 4.6 times more often when combined with asthma-like symptoms (22 % versus 4.8 %), and localize in typical places of atopic dermatitis in 5.3 % of cases, which happens more often in case of asthma-like symptoms (11.4 % versus 3.9 %).Conclusion. Studies using the ISAAC standard continuous survey showed that prevalence of non-asthma-like symptoms of atopy among adolescents in Khabarovsk and Khabarovsk Krai is higher than in most countries where this study was conducted. The frequency and structure of non-asthma-like symptoms revealed in the course of the survey is characteristic of industrially developed countries. It should be noted that the prevalence and severity of non-asthma-like symptoms in Khabarovsk is significantly higher than in the Khabarovsk rural area, however, the symptoms of non-infectious rhinitis in the countryside are more severe.